2022
DOI: 10.3390/molecules27134191
|View full text |Cite
|
Sign up to set email alerts
|

Valuable Natural Antioxidant Products Recovered from Tomatoes by Green Extraction

Abstract: Lycopene, β-carotene and ω-fatty acids are major compounds in tomatoes with known antioxidant activity, capable of preventing health disorders. The identification of potential natural sources of antioxidants, extraction efficiencies and antioxidant activity assessments are essential to promote such products to be used in the food, pharmaceutical or cosmetic industries. This work presents four added-value products recovered from tomatoes: pigmented solid oleoresin, pigmented oil and two raw extracts from superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…Some studies have demonstrated that ethyl acetate is a better extracting solvent for carotenoids than ethanol and even hexane [36]. Although a promising study, these results fell short of those obtained by Popescu et al [38] on the SC-CO 2 extraction of lycopene (1016.94 mg/100 g extract) from tomato pomace. Thus, for lycopene extraction from tomato wastes, supercritical CO 2 seems to yield the best results.…”
Section: Feed and Food Waste And Non-compliancementioning
confidence: 77%
See 1 more Smart Citation
“…Some studies have demonstrated that ethyl acetate is a better extracting solvent for carotenoids than ethanol and even hexane [36]. Although a promising study, these results fell short of those obtained by Popescu et al [38] on the SC-CO 2 extraction of lycopene (1016.94 mg/100 g extract) from tomato pomace. Thus, for lycopene extraction from tomato wastes, supercritical CO 2 seems to yield the best results.…”
Section: Feed and Food Waste And Non-compliancementioning
confidence: 77%
“…The major classes of biosolvents are (1) esters of natural organic acids (e.g., ethyl acetate and ethyl lactate), (2) fatty acid esters, (3) bioethanol, (4) terpenes compounds (e.g., eucalyptol, limonene, and others), (5) isosorbide, and (6) glycerol derivatives. These solvents are also considered green solvents since they are environmentally friendly and not harmful to humans [38][39][40].…”
Section: Green Solventsmentioning
confidence: 99%
“…Briefly, for DPPH radical scavenging activity, the reaction components created with varying volumes (10, 20, 40, 80, and 120 μL) from stock extract solutions (mg mL −1 ), 1 mL of DPPH solution (260 μM), and ethanol. The tubes were vigorously mixed, the reduction in color intensity caused by DPPH reacting with the tested antioxidant compound was read spectrophotometrically at 517 nm after 30 min in dark conditions [48] . ABTS anti radical assay was performed using the prepared ABTS radical solution with Na 2 S 2 O 8 (1 : 2) were added to test tubes and incubated dark room.…”
Section: Methodsmentioning
confidence: 99%
“…The tubes were vigorously mixed, the reduction in color intensity caused by DPPH reacting with the tested antioxidant compound was read spectrophotometrically at 517 nm after 30 min in dark conditions. [48] ABTS anti radical assay was performed using the prepared ABTS radical solution with Na 2 S 2 O 8 (1 : 2) were added to test tubes and incubated dark room. The varying volumes of extract solutions (mg mL À 1 ) were dispensed into these tubes and their volumes were made up to 3 mL with phosphate buffer (100 mM, pH = 7.4).…”
Section: Antioxidant Capacity Of Endemic Plantsmentioning
confidence: 99%
“…The characteristic peaks and functional groups of the crude extract were detected using the Fourier transform infrared spectroscopy (Nicolet iS50, Thermo Scientific, USA), with a resolution of 4 cm −1 , in the frequency range of 4000–500 cm −1 . The FTIR peak values were recorded [44] …”
Section: Methodsmentioning
confidence: 99%